2022
DOI: 10.3390/foods11193099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Flavor Profile of Roasted Germinated Wheat (Triticum aestivum L.) Beverages Served Hot and Cold Using Electronic Sensors Combined with Chemometric Statistical Analysis

Abstract: In order to fulfill the objective of the comparative flavor profiling of hot and cold serving, different concentrations of hot (hot infusion) and cold (boiled and cold serving) roasted-steamed-germinated wheat beverages were prepared in order to explore the comparative profile of the amino acids, volatiles, taste, total flavonoid content (TFC), total phenolic content (TPC), and antioxidant capacities, including 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH) and the Trolox equivalent antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 25 publications
4
17
0
Order By: Relevance
“…The water to coffee leaf ratio was 1:100. It has been previously reported that bitter taste and astringent sensation of tea beverage tended to decrease with cold serving [12].…”
Section: Coffee Leaf Tea Brewingmentioning
confidence: 90%
“…The water to coffee leaf ratio was 1:100. It has been previously reported that bitter taste and astringent sensation of tea beverage tended to decrease with cold serving [12].…”
Section: Coffee Leaf Tea Brewingmentioning
confidence: 90%
“…Wheat beverages or wheat tea, which were initially reported in Korea, are prepared via the germination, steaming, and roasting of wheat before being served as a boiled drink or an infusion ( Aung et al, 2022a , 2023 ). This type of beverage preparation is similar to methods used for herbal teas and other cereal-based teas such as barley tea.…”
Section: Wheat and Wheat-based Nonalcoholic Beveragesmentioning
confidence: 99%
“…Roasted wheat prepared by infusion and boiling methods exhibit strongly different flavor profiles and nutraceutical characteristics. For example, wheat tea served chilled is characterized by higher levels of volatiles and amino acids, stronger sourness, and a more pronounced umami taste than infused wheat tea ( Aung et al, 2022a ).…”
Section: Roastingmentioning
confidence: 99%
“…A beverage prepared from roasted germinated wheat ( Triticum aestivum L.) is a recently developed functional beverage [ 1 , 2 , 3 ]. Previous reports have described hot and cold germinated wheat beverages containing abundant volatile compounds, amino acids, and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our previous report, cold beverages were found to have a significant abundance of amino acids, contributing to sourness and umami taste traits. Conversely, hot beverages exhibited higher levels of volatile compounds, particularly hydrocarbons, which contributed to their pronounced odor profiles [ 2 ]. To obtain a marketable product, the sensory profiles and intensities of these beverages were measured using electronic sensors [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%